A relationship-based model of robot service personalization - Minsu Jang; Jaehong Kim (2015 12th International Conference on Ubiquitous Robots and Ambient Intelligence (URAI), 2015)
Knapp's relational development model states that interpersonal relationship develops in a stepwise manner going through 5 gradually intensifying stages, and shared private knowledge in each stage gets larger and deeper as a relation enters the higher stages. Based on the Knapp's model, we conceptualized a novel model of robot service personalization that is composed of two equally important and interconnected processes: relationship development and user profile modeling. Our model, called relationship-based personalization, stems from the theory entailed by the Knapp's model that a robot needs to acquire specific knowledge about a user to provide a personalized service, but the robot cannot acquire the knowledge unless it is in the proper stage of relationship with the user. In this paper, we describe the concept of our model with a short introduction to our ongoing work to realize the model.